Metabolomics analysis reveals aminoquinazolin derivative 9d-induced oxidative stress and cell cycle arrest in A549 cells. Issue 22 (24th February 2017) - Liu, Wenrui; Jin, Feng; Gao, Dan; Song, Lu; Ding, Chao; Liu, Hongxia
Abstract : An UPLC/Q-TOF MS based metabolomics approach was established to study the probable antitumor mechanism of aminoquinazolin derivative 9d, which could induce oxidative stress and cell cycle arrest in A549 lung cancer cells. Abstract : A novel aminoquinazolin derivative (named 9d), synthesized in our lab shows potential antitumor activity against A549 lung cancer cell lines. However, previous studies on the pharmacological mechanism of 9d mostly focused on cell and gene levels; the metabolic mechanism remains unknown. In this paper, an ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF MS) based metabolomics approach was established to study the probable antitumor mechanism. Q-TOF MS and MS/MS were used to identify significantly different metabolites. 22 significantly different metabolites were observed between the 9d-treated A549 lung cells group and control group. They were involved in glycerophospholipid metabolism, glutathione metabolism, phenylalanine metabolism, cysteine and methionine metabolism, and aminoacyl-tRNA biosynthesis. The results showed that glutathione level and cell-membrane components phosphatidylcholines were decreased in 9d-treated cells, while their oxidative products, oxidized glutathione and lysophosphatidylcholines, were significantly increased. Further biological investigation showed an apparent accumulation of reactive oxygen species and a decrease in mitochondrial membrane potential. The results indicated that the aminoquinazolin derivative induced oxidative stress-mediated apoptosis. Moreover, phenylalanine metabolism suggested the up-regulation ofl -phenylalanine might act as an endogenous drug carrier of 9d to improve cellular antiproliferation ability. The inhibition of aminoacyl-transfer RNA and flow cytometry results indicated that cell cycle progression was blocked in the G1 phase, which was in accordance with the results obtained from some marketed aminoquinazolin derivatives. The above results proposed that 9d could induce oxidative stress and cell cycle arrest, which finally led to cell apoptosis in A549 cells. The study supplies a rapidly and highly active strategy to investigate the antitumor mechanism of drugs, which benefits its further improvement and development.